Immediate vs. delayed toe-to-thumb transfer: Is the infection rate greater? - Ornelli, Matteo; Ruocco, Giovanni; Kaciulyte, Juste; Lazzaro, Lara; Felici, Nicola (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2019)
Background After loss of a thumb, the big toe is a possible donor site for reconstruction with wrap-around free flap and trimmed-toe transfer techniques. Early reconstructions seem to reduce the risk of post-operative infections, despite several studies that show different infection rates of the recipient site in immediate toe-to-hand transfer. The authors carried out a retrospective analysis of their experience in thumb reconstruction with big toe transfer and evaluated the results achieved with both immediate and delayed reconstructions in terms of infection occurrence.Patients and Methods From 2000 to 2017, patients who presented cut, crush and avulsion injuries in the thumb were selected and 33 toe-to-thumb transfers were performed. Patients were divided into two groups: in group A, patients underwent immediate reconstruction, while in group B delayed reconstructions were performed. The two groups received identical antimicrobial prophylaxis. Reliability of the immediate or delayed reconstruction was compared in terms of flap survival, requirement for a secondary intention healing and, in particular, rate of infection.Results 29 male and 4 female patients were treated. Toe-to-thumb transfers were performed in both groups: in group A, 8 wrap-around free flaps and 4 trimmed toe transfers; in group B, 11 wrap-around and 10 trimmed toe transfers. No flap loss occurred in either groups. No cases of infection were detected in the transferred toes.Conclusion For toe-to-thumb transfer, there are published reports of a wide range of infection rates of the recipient sites. The authors compared their results in terms of infection rate between immediate reconstruction, group A, and delayed reconstruction, group B. Immediate toe-to-thumb transfer showed equal success rates to delayed transfer. No statistically significant difference in risk of infection between the two groups was found. Results showed that the immediate reconstruction was as safe and reliable as the delayed one.
Keywords: Infection; toe transfer; thumb reconstruction